A comparison of front‐of‐pack nutrition claims between the US and EU. Issue 2 (2014) - ,; ,; ,
Abstract : Purpose – This paper aims to compare the use of front‐of‐pack nutrition claims made on 32, 257 food labels launched in 2009 in the US and the EU.Design/methodology/approach – Information from Mintel's Global New Product Database was analyzed, for 25, 417 products launched in the EU and 6, 840 in the US. The hypothesis was that "products launched in the US and EU have a different frequency of front‐of‐pack nutrition claims". Using inferential statistics, significant differences (two‐tailed Z‐ tests) in the number of claims are explored and compared to differences in legislation standards and consumer preferences.Findings – The initial analysis revealed that there were six significant differences between the presence of the seven health and nutrition claims across 16 product categories in the US and the EU. Further analysis of the 16 product categories revealed a range of significant differences between the frequency of US and EU claims.Originality/value – The emerging relevance of front‐of‐pack nutrition labeling as a marketing tool makes such differences pertinent. This paper marks the first systematic comparison of the use of claims between the US and EU.